Utilização de resíduos de borracha de pneus em misturas de solo-cimento visando a aplicação em obras de estradas - (:unkn) unknown (Universidade Federal do Pampa, 2013)
The soil stabilization always been recurrent since the first floors built, but have become more frequent in recent decades. Thus, new techniques were developed such as the stabilization of chemical stabilization by mixing and soil-cement has been used on roads in order to add the soil improvement compared to factors such as plastic deformation, improving the granulometry of the material and increases the resistance of soil. Also, there is a need to reuse new alternative materials that could be used in paving road. This study aimed to evaluate the mechanical effect of fibers scrape tires in mixtures of soil-cement. As for this, initially collected samples of various types of soils, derived from three sites located in the municipality of loan Alegrete / RS. Then, from the results of the geotechnical characterization tests, was chosen for the best development of this work, one type of soil collected from one of the mines. Also, samples were collected waste tires zest, plus the acquisition of pozzolan cement. After that were prepared mixtures of soil-cement and soil-cement-fiber rubber tire scrapes. Thus for this research adopted the proportions of soil-cement mixture of 92% -8% cement. As for mixing soil-cement-fiber shaving tire, have been adopted in the proportions (92% - 5% - 3%) (91% - 8% - 1%) (89% - 8% - 3% ), (87% - 8% - 5%) (82% - 8% - 10%). Subsequently, for various mixtures assays were performed compaction, expansion tests, assays California bearing ratio and simple compression tests. For this study, the experimental results show that the mixture of soil and soil-cement-fiber cement-rubber tire scrapings, for the weight ratio: 91% -8% -1%, exhibited the best results.
Keywords: Civil engineering; Stabilization of soils; Soil-cement; Asphalt paving; Rubber tires; CNPQ::ENGENHARIAS; Engenharia civil; Estabilização dos solos; Solo-cimento; Pavimentação asfáltica; Borracha de pneus